Hédi Bouraoui, poète paysagiste dans Livr'errance - Grossman, Simone (Revue CMC Review, 2018)
The article focuses on the dialogue the poet Hédi Bouraoui establishes with a number of visual artists whose works appear on the title pages of sections of this collection. It reflects on the ways in which the verbal and visual arts interact and complement each other.